2017
DOI: 10.1080/19440049.2017.1368722
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Fusarium toxins in functional vegetable milks applying salting-out-assisted liquid–liquid extraction combined with ultra-high-performance liquid chromatography tandem mass spectrometry

Abstract: Vegetable milks are considered as functional foods due to their physiological benefits. Although the consumption of these products has significantly increased, they have received little attention in legislation with regard to contaminants. However, they may contain mycotoxins resulting from the use of contaminated raw materials. In this work, ultra-high-performance liquid chromatography tandem mass spectrometry has been proposed for the determination of the most relevant Fusarium toxins (fumonisin B and B, HT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Several works studied the occurrence of different mycotoxins in oat, soy, and rice-based milks, as they are the most consumed worldwide [32][33][34][35]. Miró-Abella et al [32] reported, for the first time, the presence of mycotoxins in plant-based milks and found DON, OTA, ZEN, and T-2 toxin together with aflatoxins B1, B2, G1, and G2 present in certain samples, with oat-based beverages being the most frequently contaminated.…”
Section: Plant-based Milksmentioning
confidence: 99%
“…Several works studied the occurrence of different mycotoxins in oat, soy, and rice-based milks, as they are the most consumed worldwide [32][33][34][35]. Miró-Abella et al [32] reported, for the first time, the presence of mycotoxins in plant-based milks and found DON, OTA, ZEN, and T-2 toxin together with aflatoxins B1, B2, G1, and G2 present in certain samples, with oat-based beverages being the most frequently contaminated.…”
Section: Plant-based Milksmentioning
confidence: 99%
“…Traditionally, mycotoxin determination has mainly been performed by chromatographic techniques, including HPLC-UV/Vis [ 15 ], HPLC-FLD [ 16 ] or liquid chromatography/mass spectrometry (LC/MS) [ 17 ], in combination with effective separation approaches to avoid matrix disturbance. Most pretreatment approaches involve liquid-liquid extraction [ 18 ], solid-phase extraction [ 19 ], liquid-phase microextration [ 20 ] or an immune-affinity column [ 21 ]. However, these methods typically suffer from some limitations, such as low sensitivity, poor repeatability, and increased cost and time.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, one of the main advantages of mass spectrometry detectors is the possibility of performing multiplex analysis, not only for different mycotoxins [48,49,50,53,54,57,58,59,60,61,64,65,66,67,71,72,73,74,77,79,80,187], but also when combined with varied metabolites. Growth regulators, antibiotics, pesticides [51,70,75], and other fungal metabolites [63,68], were simultaneously identified in analysis capable of assessing up to 74 and 90 compounds [62,78]. Mass spectrometry has also been used for assessing mycotoxin transfer from feed to organs and tissue in poultry [80] The importance of novel analytical methods relies on the low sensitivities achieved within a relatively short detection time.…”
Section: Chromatographic Detection Of Fumonisin B1mentioning
confidence: 99%